INTERNALIZATION OF DISCIPLINARY CHARACTER VALUES THROUGH PAI LEARNING - Rahman Hakim, Arif (ILJ: Islamic Learning Journal, 2023)
The purpose of this research is to describe the Internalization of disciplinary character values, how the Internalization of disciplinary character values and what are the inhibiting and supporting factors in the Internalization of disciplinary character values at Primaganda Jombang High School, The research design used in this research is a case study. This research aims to develop an efficient working method, meaning that the researcher conducts an in-depth study of a case, the conclusion is limited to a particular case. The collection technique uses interviews, observation and documentation, while the validity of the data in this study uses triangulation, namely triangulation of sources and techniques. The results in this study show that 1) Internalization of student discipline character values at Primaganda Jombang High School includes through Planning activities: including, modeling good behavior, not being late for teaching, making sanctions. Implementation: includes following the recitation before entering school, praying dhuha and dhuhur (in congregation) and following the organization at school. Evaluation: includes assessment of student learning such as activeness, creativity, understanding, student involvement in learning, especially mental, emotional and social involvement, 2) The inhibiting and supporting factors in the internalization of student discipline character values at Primaganda Jombang High School include: The role of the principal, the active role of the teacher, student awareness and the pesantren environment.